PREPARING TEACHERS FOR INCLUSION IN LITHUANIA: TEACHER EDUCATORS’ APPROACHES TO DIVERSITY AND EXISTING CHALLENGES - Chu, Lingyi; Khetsuriani, Nano (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2024)
Inclusive education is a universal pedagogical trend, covering a broad range of research areas such as race, ethnicity, gender, culture, language, religion, and ability. An inclusive system concerns the rights, social justice, and equity within education for all, especially the marginalised groups (UNICEF, 2022). Lithuania has officially rolled out new legislation (in 2011) and structural changes (in 2024) to its educational system, moving it from a multi-track system to an inclusive one. However, teachers have reported implementation difficulties such as differentiating teaching methods, fostering student socialisation, and lacking multiprofessional collaboration and dialogue with parents (Lakkala et al., 2019). Contextual urgency lies in the changing demographics of the student body and impacts the reconsideration of diversity and inclusion in Lithuanian classrooms. This study focuses on teacher educators' (TEs) perspectives at a major teacher training university in Lithuania. Semi-structured interviews were conducted with faculty members to understand how diversity and inclusion are understood, interpreted, and implemented within the faculty. This research revealed current practices within teacher training regarding diversity, highlighting strengths, challenges, and potential enhancements. Critical implications for preparing future educators for inclusive classrooms are discussed.